Patient selection for spinal cord stimulation: The importance of an integrated assessment of clinical and psychosocial factors. (2nd August 2022) - Thomson, Simon; Helsen, Nicky; Prangnell, Simon; Paroli, Mery; Baranidharan, Ganesan; Belaïd, Hayat; Billet, Bart; Eldabe, Sam; De Carolis, Giuliano; Demartini, Laura; Gatzinsky, Kliment; Kallewaard, Jan Willem; et al.
Abstract: Background: A previously developed educational e‐health tool considers both clinical and psychosocial factors when selecting patients with chronic pain for spinal cord stimulation (SCS). The validity of the composite recommendations was evaluated in a retrospective study, demonstrating a strong relationship with patient outcomes after SCS. Methods: An additional retrospective analysis was performed to determine the added value of a psychosocial evaluation as part of the decision‐making process on SCS. Data concerned 482 patients who were considered for SCS in 2018–2019. The analysis focused on the relationship between the different layers of the tool recommendations (clinical, psychosocial, composite) with trial results and patient outcomes at 6 months after SCS. Of the initial study population, 381 patients underwent SCS and had follow‐up data on at least one of three pain‐related outcome measures. Results: Pain improvement was observed in 76% of the patients for whom SCS was strongly recommended based on merely the clinical aspects. This percentage varied by the level of psychosocial problems and ranged from 86% in patients without any compromising psychosocial factors to 60% in those with severe problems. Similarly, the severity of psychosocial problems affected trial results in patients for whom SCS was either recommended or strongly recommended. Conclusions: The strong relationship between psychosocial factors embedded in the SCS e‐health tool and patient outcomes supports an integrated and multidisciplinary approach in the selection of patients for SCS. The educational e‐health tool, combining both clinical and psychosocial aspects, is believed to be helpful for further education and implementation of this approach. Significance statement: This study confirms the relevance of the psychosocial factors embedded in the educational SCS e‐health tool (https://scstool.org/ ). The strong relationship between the severity of psychosocial factors with patient outcomes supports conducting a comprehensive psychological and behavioural assessment when determining the eligibility of patients for SCS.